Resolving inherent safety conflict using quantitative and qualitative technique - Zainal Abidin, M. (Elsevier Ltd, 2016)
Inherent safety strategy is an integral component of all engineering activities that strive towards simpler, cheaper, and safer processes. This also implies that less energy and maintenance are required and less waste and pollution are produced, which are the underlying principles of the chemical process industry. However, potential hazards that arise from inherently safer design (ISD) modification must be evaluated carefully to avoid misapplication of the inherent safer design strategy. In the previous work, the author developed a qualitative review tool, the Three-Stage ISD Matrix Tool, with the objective to help assessors understand the impact of ISD modification. In this paper, the Three-Stage ISD Matrix Tool will be combined with quantitative technique, Hazard Identification and Ranking System methodology, with the aim to quantify the impact of ISD modification. Two case studies will be presented in order to demonstrate the applicability of this approach. In the first case study, we show how this technique is capable of identifying the potential hazard that arise from a modification of Union Carbide India Limited facilities prior to the Bhopal accident. In the second case study, we show the applicability of this technique to select the safer options for ammonia storage system considering the fatalities potential and environmental impact. The results show that the combination of qualitative with quantitative technique can help assessors to effectively perceive the total impact of ISD modification. Â© 2016 Elsevier Ltd